2015
DOI: 10.1037/xlm0000116
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, intentionality, and mind wandering: Implications for assessments of task-unrelated thought.

Abstract: Researchers of mind wandering frequently assume that (a) participants are motivated to do well on the tasks they are given, and (b) task-unrelated thoughts (TUTs) that occur during task performance reflect unintentional, unwanted thoughts that occur despite participants' best intentions to maintain task-focus. Given the relatively boring and tedious nature of most mind-wandering tasks, however, there is the possibility that some participants have little motivation to do well on such tasks, and that this lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
157
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(178 citation statements)
references
References 51 publications
(95 reference statements)
13
157
3
Order By: Relevance
“…Although theoretical consideration of the intentionality of mind wandering has largely been absent over the past few decades, in a recent series of studies some researchers have revisited the distinction between intentional and unintentional mind wandering (Forster & Lavie, 2009; Seli, Cheyne, et al, 2015; Seli, Risko, Purdon, & Smilek, 2016; Seli, Risko, & Smilek, 2016b; Seli, Smallwood, Cheyne, & Smilek, 2015; Seli, Wammes, et al, 2015). Critically, in some of this research it has been shown that these two types of mind wandering appear to reflect unique cognitive experiences.…”
Section: The Level Of Intentionality Of Mind Wandering: Intentional Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Although theoretical consideration of the intentionality of mind wandering has largely been absent over the past few decades, in a recent series of studies some researchers have revisited the distinction between intentional and unintentional mind wandering (Forster & Lavie, 2009; Seli, Cheyne, et al, 2015; Seli, Risko, Purdon, & Smilek, 2016; Seli, Risko, & Smilek, 2016b; Seli, Smallwood, Cheyne, & Smilek, 2015; Seli, Wammes, et al, 2015). Critically, in some of this research it has been shown that these two types of mind wandering appear to reflect unique cognitive experiences.…”
Section: The Level Of Intentionality Of Mind Wandering: Intentional Vmentioning
confidence: 99%
“…In the present article, we focus on two important dimensions of mind wandering: intentionality (i.e., whether it is engaged with intention) and meta-awareness (i.e., whether an individual is aware of its occurrence). Although the meta-awareness dimension has long played a pivotal role in theoretical accounts of mind wandering (Schooler, 2002), only recently have researchers begun to focus more prominently on the theoretical importance of the intentionality dimension (Forster & Lavie, 2009; Seli, Cheyne, Xu, Purdon, & Smilek, 2015; Seli, Risko, & Smilek, 2016b; Seli, Risko, Smilek, & Schacter, 2016; Seli, Wammes, Risko, & Smilek, 2015). However, at face value, the dimensions of intentionality and meta-awareness appear to share considerable overlap, and there remains the possibility that they may even be completely redundant.…”
mentioning
confidence: 99%
“…As people spend more time on a task, fatigue and boredom increase, making it more likely for their minds to drift off Metcalfe & Xu, 2016;Smallwood et al, 2003;Smallwood, Riby, Heim, & Davies, 2006). Work on individual differences also suggests that motivation and interest alter one's tendency to mind wander (Antrobus, Singer, & Greenberg, 1966;Grodsky & Giambra, 1990-1991Jackson & Balota, 2012;Krawietz, Tamplin, Radvansky, 2012;Seli, Cheyne, Xu, Purdon, & Smilek, 2015;Unsworth et al, 2012;Unsworth & McMillan, 2013). For example, Unsworth and McMillan proposed a model in which interest predicted motivation, and motivation in turn predicted mind wandering.…”
mentioning
confidence: 99%
“…For example, the often-used Sustained Attention to Response Task (SART) requires participants to respond to highly frequent targets (digits 1 to 9) and withhold responses to infrequent non-targets (e.g., the digit 3), while being randomly probed whether they are on-task or off-task. The proportion of probes with reported mind-wandering can be relatively low even in young participants, (McVay & Kane, 2009;Smallwood, O'Connor, Sudberry, Haskell, & Ballantyne, 2004), and recent findings indicate that a fairly large proportion of thoughts rated as off-task (i.e., 34% -41%) are actually deliberate task-unrelated thoughts that participants intentionally engage in for various reasons (e.g., boredom) (Seli, Cheyne, Xu, Purdon, & Smilek, 2015;. Consequently, using the standard version of the SART for assessing the spontaneous retrieval deficit hypothesis may be problematic given the strong emphasis of this hypothesis on the reduction in spontaneous rather than intentional mind-wandering in aMCI.…”
mentioning
confidence: 99%